124 Low-Back Pain Relief With a New 32-Contact Surgical Lead and Neural Targeting Algorithm. (1st August 2016) - Pilitsis, Julie G.; Barolat, Giancarlo; Rosenow, Joshua M.; Brennan, James J.; Bailey, Alexander S.; Epstein, Jeffrey M.; Hammond, Blake; Metzger, Clark; Huynh, Dat; Lechleiter, Kristen; Mekel-Bobrov, Nitzan
Abstract: INTRODUCTION: Treatment of low-back pain using Spinal Cord Stimulation (SCS) has been historically challenging. Advances in surgical leads and programming capabilities have been thought to potentially enable improved low-back pain relief using SCS. A recently introduced 32-contact surgical lead, which couples multiple independent current control (MICC) and anatomically based neural targeting stimulation algorithms, allows for patient-specific programming optimization. We present here a real-world, observational study of this 32-contact surgical lead. METHODS: A multicenter, consecutive, observational study of a new 32-contact surgical lead was conducted using the Precision Spectra SCS System (Boston Scientific) in 100 subjects out to 12 months postimplant. We examined medical history, procedural information, programming parameters, and clinical outcomes including pain reduction (NRS), activities of daily living, and change in pain medications. RESULTS: Surgical lead placement distribution was between T7 and L2, with most at T9 (26%). A mean reduction of 5.1 points (SD 2.15, P < .001) from 7.8 (baseline) to 2.6 in overall pain was observed. A subset of subjects reporting low-back pain only exhibited a mean decrease of 6.0 points (SD 2.12, P < .001) from 8.3 (baseline) to 2.2. Of these, 83.1% of subjects showed 50% back pain reduction. Increases in activities of daily living and reduction in pain medication usage were also observed in a majority of subjects. CONCLUSION: Subjects implanted with a 32-contact surgical lead using a neural targeting algorithm demonstrated significant low-back pain reduction. These results support the postulate that advanced surgical leads and programming capabilities can foster improved low-back pain relief in subjects treated using SCS.